Infrastructural Barriers to e-Health Implementation in Developing Countries: - Qureshi, Qamar Afaq; Shah, Bahadar; Najeebullah, Dr.; Kundi, Ghulam Muhammad; Nawaz, A.; Miankhel, Amanullah Khan; Chishti, Kamran Ahmad; Qureshi, Najam Afaq (European Journal of Sustainable Development, 2013)
Infrastructure is the backbone of every CBISirrespective of the field or organization.Digital technologies are not only expensive but also demand professionalism for successfulexecution of e-Projects. However the availability of basic infrastructure is indispensable.The research reports that infrastructural issues are dominating the research on e-projects inall organizations including health sector. Thisbecomes more critical in the background ofdeveloping states like Pakistan. This paper aims at pinpointing the widely reported barriersto e-health projects emanating from the infrastructural availability and its maintenance withfocus on developing countries